Progress in Cryptology -- AFRICACRYPT 2009 Second International Conference on Cryptology in Africa, Gammarth, Tunisia, June 21-25, 2009, Proceedings - Preneel, Bart (Security and Cryptology, 2009)
This book constitutes the proceedings of the Second International Conference on Cryptology in Africa, AFRICACRYPT 2009, held in Gammarth, Tunisia, on June 21-25, 2009. The 25 papers presented together with one invited talk were carefully reviewed and selected from 70 submissions. The topics covered are hash functions, block ciphers, asymmetric encryption, digital signatures, asymmetric encryption and anonymity, key agreement protocols, cryptographic protocols, efficient implementations, and implementation attacks.